VD_FINDINFO HC / 2012 / 165 vom 23. Januar 2012 - VD Tribunal cantonal (2012)
NOUVEAU MOYEN DE FAIT, PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONJOINT | 163 al. 1 CC, 176 al. 1 CC, 272 CPC (CH), 317 al. 1 CPC (CH)